The explosion of digital storytelling. Creator's perspective and creative processes on new narrative forms - Sánchez López, Iván; Pérez Rodríguez, María Amor; Fandos Igado, Manuel (Elservier Inc, 2020)
Networked digital narratives are developed in a society marked by distrust in meta-narratives, liquidity and tension between Mass Media and New Media. This research aims to delve into these narratives from the creators’ perspective, analyzing new formats, authors and creative processes that are put into practice. For that purpose, the applied methodology combines in-depth interviews with creators with discourse analysis, and arts based research with the technique of the research journal. The results reveal an overflow of the classical conception of narrative, a trend towards convergence, and the dominance of visual and sequential creative thinking over alphabetical-continuous thinking. It also shows a series of clues for the creation of digital narratives: interactivity, hypermedia, transmedia, virtuality and connectivity. Finally, we highlight that creators do not have preestablished guidelines and follow the procedure of trial and error for the construction of their narratives.
Keywords: education; digital narrative; interactivity; new media; digital storytelling; creators; Scopus; JCR